O desastre ambiental barragem de resultante do rompimento da Fundão: possibilidades de reparação dos atingidos no Brasil e no Sistema Interamericano de Proteção dos Direitos Humanos - Martins, Fernanda Rezende (2021)
The present study has as its central theme the study of disaster risks in mining activities and the (im)possibility of complete reparation for the victims of the Fundão dam collapse, in 2015, based on the measures taken by Brazil or, if insufficient, under the IAHRS. The work is divided into four chapters, all aimed at discussing the possibility of reparation for victims of dam failure. Therefore, the first part considers the constant transformation of the man vs. nature relationship, which leads the human being to consolidate itself as the main protagonist of environmental disasters, emphasizing the influence of this context on the Brazilian extractive sector. The second chapter explores disaster risk management in Brazil and its legislative measures relating to mining. In the third part, Mariana's case is explained, considering all stages (prevention, emergency response, compensation and reconstruction), highlighting the omissions and violations that occurred. Finally, in the fourth part, it is expected to develop the possibilities offered by the current scenario of the IAHRS for the search for a comprehensive reparation for those affected, in case domestic action is insufficient. Therefore, the dissertation is based on the hypothetical-deductive method of analysis, with a qualitative approach, following bibliographical and documentary procedures. In the end, it is concluded that, to the extent that Brazil's internal limitations for adequate reparation for the victims of the disruption are verified, it is possible that comprehensive reparation will be sought at the regional level, since the country is linked to the Inter-American forum and meets the requirements for your accountability. Still, it appears that such a possibility goes far beyond formal feasibility, being possible mainly in light of the current movement of enshrining the right to the environment as autonomous and justiciable, which brings the opportunity that the internationalization of environmental problems involving the mining sector can, finally, to make the country evolve together with the System.